2024
DOI: 10.1021/acsenergylett.3c02779
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Assessment of Hysteresis in Perovskite Solar Cells

Enrique H. Balaguera,
Juan Bisquert

Abstract: Halide perovskite materials have reached important milestones in the photovoltaic field, positioning them as realistic alternatives to conventional solar cells. However, unavoidable kinetic phenomena have represented a major concern for reliable steady-state performance assessment from standard current–voltage measurements. In particular, the dynamic hysteresis of current–voltage curves requires relatively long stabilization to achieve a credible figure for the power conversion efficiency. Hysteresis is cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 59 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…S1 in the ESI†), which has been frequently reported for many perovskite solar cells. 49–51 Nevertheless, it is important to note that, 2D perovskite passivated with MXene helps to reduce the pinhole defects, and subsequently carrier recombination which leads to enhance the current density.…”
Section: Resultsmentioning
confidence: 99%
“…S1 in the ESI†), which has been frequently reported for many perovskite solar cells. 49–51 Nevertheless, it is important to note that, 2D perovskite passivated with MXene helps to reduce the pinhole defects, and subsequently carrier recombination which leads to enhance the current density.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21] Within this context, recent frameworks have been put forward to explore the frequency domain characteristics of PSCs. [22][23][24] Valuable research in the field has identified some of the parameters affecting hysteresis such as scan rate, [25][26][27][28] device architecture, [29][30][31] chemistry of the perovskite layer, 12,[32][33][34] as well as the electron-transport layer (ETL) and hole-transport layer (HTL). [35][36][37][38][39] For n-i-p architectures, the choice of ETL has been shown to exert a heavy influence over the microstructure of the perovskite layer, as well as the corresponding PSC performance with respect to efficiency, hysteresis and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid lead halide perovskites (OILHPs) have attracted significant interest in the past years due to their outstanding performance as solar absorbers in photovoltaics [ 1 , 2 , 3 , 4 , 5 ]. The long carrier lifetime of photogenerated carriers is a crucial factor for excellent optoelectronic performance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%